LANGUAGE ASSESSMENT LITERACY DEVELOPMENT: A STUDENT-TEACHERâS EXPERIENCES IN TEACHING PRACTICE PROGRAM - Prasetyo, Agustinus Hardi (LLT Journal: A Journal on Language and Language Teaching, 2018)
The development of a student-teacherâs language assessment literacy was viewed through her experiences in conducting teaching practice in one of the senior high schools in Yogyakarta, Indonesia. An interview was conducted to explore the experiences taking place in the teaching-practice in relation to the language assessment literacy development. It was found out that the experiences were understood as mostly dealing with administrative tasks and there is a need of more knowledge in administrative matter in teaching and assessment. From the results of the study it was obvious that further studies need to be conducted to explore the role of teaching-practice in the development of student-teaching language assessment literacy. More participants and multiple data collection methods in a longitudinal study are needed to help student-teachers to be more assessment literate, which in turn helps them to be better teachers.DOI:Â doi.org/10.24071/llt.2018.210209